Development of decentralised apps (dapps) using blockchain technology to improve insurance process in Malaysia - Laan, Wei Yi (2022)

(untitled)
Current insurance industry is having complicated process as well as heavily human involved. Parties involved usually consists of insurers, insured, auditor and 3rd party services. With inefficient processing time, lack of trust and lack of transparency, it prone to have reduce user experience. Insurance companies are also actively seeking a better solution. To this end, we proposed a decentralized application that build on blockchain network as a solution to the problems. Blockchain is an emerging technology that brings transparency and security to data storage and transparency. In this paper, we will introduce basic background of traditional insurance and blockchain as well as discuss how the integration of blockchain will bring positive impact to insurance domain. Furthermore, we will also indicate our system design. Our system aims to enhance insurance policy processing and claim handling with the least of human intervention. This solution is also able to avoids certain type of fraud with proper validation. The result of this project is a developed prototype of decentralized application on Ethereum blockchain.